2015
DOI: 10.1007/s40091-015-0106-5
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and flexural behavior of triangular and T-reinforced concrete beams

Abstract: The paper studied the behavior of reinforced concrete triangular and T-beams. Three reinforced concrete beams were tested experimentally and analyzed analytically using the finite element method. Their reliability was also assessed using the reliability index approach. The results showed that the finite element vertical displacements compared well with those obtained experimentally. They also showed that the vertical displacements obtained using the finite element method were larger than those obtained experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…Al-Ansari [6] studied the reliability of reinforced concrete triangular and T-beams using the reliability index approach. Their behavior was also investigated experimentally and analytically.…”
Section: Introductionmentioning
confidence: 99%
“…Al-Ansari [6] studied the reliability of reinforced concrete triangular and T-beams using the reliability index approach. Their behavior was also investigated experimentally and analytically.…”
Section: Introductionmentioning
confidence: 99%
“…After calculating the values of the bending moment and the applied live and dead loads, a limit function as in Eqns. (10) and (11) are considered.…”
Section: The Safety Surface Of Bending-torsionmentioning
confidence: 99%
“…Al-Ansari et al applied experimental and numerical methods (FEM) in order to study the flexural behavior of T and rectangular concrete beams. Their experimental study was compared with the FEM analysis results for verifying the FEM code, which showed that the FEM result of rectangular beam is more safer than an experimental result for T-beam [10]. Bastidas et al in 2018 studied the combined effects of chloride-induced corrosion, climate change and cyclic loading with a stochastic model.The results of this study show that the climate change lifetime of structure by roughly 1.4 -2.3% [11].…”
Section: Introductionmentioning
confidence: 99%
“…The work [2] considers experimental and theoretical calculation of the reliability index for reinforced concrete beams with different cross-sections. The paper [3] describes the calculation of the non-failure probability (reliability index) of reinforced concrete beams with carbon-fiber reinforced polymers (CFRP).…”
Section: Introductionmentioning
confidence: 99%